Letter to Jeanne Fox from Julie Altschuler - Julie Altschuler:::::: (1970)
In this November 13, 1970 letter from Assemblyman Alan Sieroty's office, secretary Julie Altshuler informs Jeanne Fox that a list of women's names is attached for inclusion in the upcoming Key Women luncheon in December.